Pengaruh Pengetahuan Akuntansi, Pengalaman Usaha Dan Skala Usaha Terhadap Persepsi Penggunaan Informasi Akuntansi Pada Pelaku UMKM Kota Medan - Nurhajelin; Harahap, Junita Putri Rajana (JURNAL AKUNTANSI AUDIT DAN PERPAJAKAN INDONESIA (JAAPI), 2023)
UMKM have an important role because they are able to create business fields to support daily economic needs. Accounting knowledge and business experience are one of the factors in developing a business. The purpose of this research is to find out whether Accounting Knowledge, Business Experience and Business Scale affect the Use of Accounting Information in UMKM in Medan City. This type of research is quantitative research using primary data in the form of a questionnaire. The population in this study are 1,771 UMKM in the city of Medan. The sample used in this study used simple random sampling, namely as many as 80 samples with several criteria. The data analysis method used is multiple linear regression and hypothesis testing using SPSS. The results showed that accounting knowledge and business scale had a partial and significant effect on the use of accounting information, while business experience had no partial and significant effect on the use of accounting information. Accounting knowledge, business experience and business scale simultaneously and significantly influence the use of accounting information.